Soil Carbon Sequestration Resulting from Biosolids Application - Silvana I. Torri; Rodrigo Studart Corrêa; Giancarlo Renella (Applied and Environmental Soil Science)
Carbon (C) sequestration in soils through the increase of the soil organic carbon (SOC) pool has generated broad interest to mitigate the effects of climate change. Biosolids soil application may represent a persistent increase in the SOC pool. While a vast literature is available on the value of biosolids as a soil conditioner or nutrient source in agricultural systems, there is still limited knowledge on soil sequestration mechanisms of biosolids-borne C or the main factors influencing this capacity. The emerging challenges posed by global environmental changes and the stringent needs to enhance C storage call for more research on the potential of soil biosolids incorporation as a sustainable C storage practice. This review addresses the potential of C sequestration of agricultural soils and opencast mines amended with biosolids and its biological regulation.